2001
DOI: 10.1592/phco.21.10.95s.34532
|View full text |Cite
|
Sign up to set email alerts
|

New Directions in Antiinfective Therapy for Community‐Acquired Pneumonia in the Emergency Department

Abstract: The emergency department is becoming an increasingly important setting for the management of community-acquired pneumonia (CAP). This trend reflects the shortened hospital stays and decreased mortality among elderly hospitalized patients resulting from rapid administration of antimicrobials. In addition, decisions about the site of care (inpatient vs outpatient) and antimicrobial therapy frequently are made in the emergency department. Recent research and subsequent clinical guidelines may help with these deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Pneumonia accounts for a large proportion of ED visits in the United States and is associated with a high rate of morbidity and mortality 8–10 . We observed that rates of pneumonia were disproportionately higher among blacks and the elderly.…”
Section: Discussionmentioning
confidence: 71%
“…Pneumonia accounts for a large proportion of ED visits in the United States and is associated with a high rate of morbidity and mortality 8–10 . We observed that rates of pneumonia were disproportionately higher among blacks and the elderly.…”
Section: Discussionmentioning
confidence: 71%
“…In general, organisms considered resistant by microbiological standards increase the frequency of treatment failure, relapse, and mortality (examples are observed with Mycobacterium tuberculosis [O'Brien, 1994;Portaels et al, 1999], S. pneumoniae [Moran, 2001], Staphylococcus aureus , Pseudomonas aeruginosa [Carmeli et al, 1999;Olson et al, 1985], and Neisseria gonorrhoeae ). For a given patient, however, treatment may be successful even though the infection is caused by a pathogen deemed to be resistant by breakpoint criteria .…”
Section: The Resistance Problemmentioning
confidence: 99%
“…A number of severity-related variables were associated with an increased probability of receipt of IV agents, however, differences between hospital sites persisted despite controlling for differences in case mix. While an initial dose of IV antibiotics in the ED has been suggested as part of an outpatient management strategy (Moran 2001), further study is required to determine the extent to which such use may prevent unnecessary hospitalization, and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients at low risk treated on an outpatient basis receive predominantly oral antibiotics, while the majority of higher risk hospitalized subjects initially receive intravenously administered antibiotics (Gilbert et al 1998). While oral treatment is the norm among nonhospitalized patients, there is some support for initial treatment with parenteral antibiotics in the emergency department (ED) followed by oral administration (Moran 2001). The extent of this practice is unknown.…”
Section: Introductionmentioning
confidence: 99%